Detection of pulmonary hypertension by Doppler echocardiography of the inferior vena cava in chronic airflow obstruction. Issue 5 (May 1989) - Laaban, J P; Diebold, B; Lafay, M; Rochemaure, J; Peronneau, P
Abstract : Pulsed Doppler echocardiography of the inferior vena cava is an accurate method for the diagnosis of tricuspid regurgitation and impaired right ventricular compliance, two features of pulmonary hypertension. The purpose of this study was to assess the value of Doppler echocardiography of the inferior vena cava for the detection of pulmonary arterial hypertension in patients with chronic obstructive lung disease. Pulse Doppler echocardiography of the inferior vena cava and right heart catheterisation were performed in 29 patients with severe chronic obstructive lung disease. The mean pulmonary arterial pressure was 27 (10) mm Hg for the entire group; 62% of patients (18/29) had pulmonary arterial hypertension (mean pulmonary arterial pressure greater than 20 mm Hg). An adequate Doppler signal could be obtained in 25 of the 29 patients (86%). Pulsed Doppler echocardiography of the inferior vena cava gave normal results in 10 patients and disclosed tricuspid regurgitation in seven patients, impaired right ventricular compliance in seven patients, and both of these abnormalities in one patient. An abnormal Doppler echocardiogram of the inferior vena cava (tricuspid regurgitation or impaired right ventricular compliance, or both) predicted the presence of pulmonary arterial hypertension with a sensitivity of 87% and a specificity of 80%. These results suggest that pulsed Doppler echocardiography of the inferior vena cava may be a useful though imperfect method of detecting pulmonary arterial hypertension in patients with chronic obstructive lung disease.